CLOUD COMPUTING SECURITY ISSUES AND CHALLENGES - Ahmed, Aqeel; Kumar, Sandeep; Shah, Azhar Ali; Bhutto, Arifa (Tropical Scientific Journal, 2023)
Objective: Cloud computing security is a mushrooming service that has identical features to conventional IT security. It offers protecting sensitive information from data theft, loss and destruction. One of the advantages of cloud services is that you can work at scale. But is the system secured properly? The system is vulnerable to attacks from many directions e.g., unsecure network, data losses, data breaches, cyber-attacks, reduced control etc. Therefore, we have new opportunities to deliver security solutions that meet new challenges. This paper discusses on these issues and provide remedial suggestions which can be focused on improving the system. Research Method: This paper presented a details of issues faced during cloud computing security through a comprehensive literature review. Findings: The main drawback of current cloud service implementations is that they are unable to offer high levels of security. Transmission paths that involve a third party must also meet a security requirement. To guarantee a high level of security, privacy, authenticity, integration, speed, scalability, and dependability when using cloud services, many factors must be improved. Perhaps a promising area of research to address cloud computing security issues will be an automated service level agreement, a third-party trustee, or a new extension. Originality: This study will help the practitioner in understanding the challenges faced in cloud computing security. It will support in developing a propoer security system to an efficient cloud computing system.